A high-temperature parallel double-Fabry–Pérot interferometer sensor based on the Vernier effect. (1st June 2021) - Yi, G; Su, H; Zhang, Y; Ma, K
Abstract: A high-temperature sensor based on a parallel double-Fabry–Pérot interferometer (FPI) structure is reported. The Vernier effect is produced in the parallel double-FPI structure to enhance the temperature sensitivity. The sensing FPI (SFPI) is fabricated by fused splicing of a suspended-core fiber and a single-mode fiber (SMF). Tip package technology for the SFPI means that the sensing part is not subjected to disturbance from the external medium. The reference FPI (RFPI) is an air cavity constructed by inserting two SMFs into a hollow core tube; thus the magnification of the Vernier effect can be easily adjusted by precise control of the cavity length of the RFPI. Temperature tests were carried out from 50 °C to 800 °C to assess sensing capabilities, with the RFPI being fixed at room temperature while the SFPI was exposed to the measuring environment. The easily fabricated parallel double-FPI structure proved to have high sensitivity, good stability and repeatability over a large dynamic temperature range, conducive to temperature measurement under harsh conditions and mass production.